VD_FINDINFO Décision / 2019 / 295 vom 8. April 2019 - VD Tribunal cantonal (2019)
DÉTENTION PROVISOIRE, RISQUE DE RÉCIDIVE, PROPORTIONNALITÉ, SOUPÇON, VIOLENCE DOMESTIQUE | 221 al. 1 let. c CPP (CH), 221 al. 2 CPP (CH), 237 CPP (CH)